Penilaian Kinerja Keuangan Perusahaan dengan Menggunakan Metode Market Value Added (MVA) - Jacinta Winarto (Jurnal Manajemen Maranatha, 2005)
Since traditional accounting method could lead to misleading conclusion, Stern, Stewart & Co created a new method named Market Value Added (MVA). MVA assists managers to focus on valuable activities and to evaluate performance based on company performance evaluation maximizer. MVA is an absolute substraction between company market value with invested capital. MVA reflects public shares times substraction of share price and shares economic book value of each shares. The MVA could be a better reference for sharehoders for considering whether a company could give profit or loss against invested capital. Shareholders could calculate addition or substract on true value of company real condition with the MVA method.